2018
DOI: 10.1161/strokeaha.118.020814
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Enriched Environment and Task-Specific Reach Training on Poststroke Recovery of Motor Function

Abstract: Background and Purpose-Reach training in concert with environmental enrichment provides functional benefits after experimental stroke in rats. The present study extended these findings by assessing whether intensive task-specific reach training or enrichment initiated alone would provide similar functional benefit. Additionally, we investigated whether the 70% recovery rule, or a combined model of initial poststroke impairment, cortical infarct volume, and rehabilitation intensity, could predict recovery in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 56 publications
(101 reference statements)
1
36
0
Order By: Relevance
“…EE alone is not effective in promoting recovery of skilled forelimb movements (e.g., reaching; Grabowski et al, 1993 ), since there is no opportunity to engage in this activity in standard EE configurations. As such, to fill this void our group adds a daily reaching task component to EE which dramatically improves the level of recovery provided by EE (Biernaskie and Corbett, 2001 ; Biernaskie et al, 2004 ; Jeffers and Corbett, 2018 ). Thus, the ideal definition of EE, unlike typical stroke rehabilitation in the clinic, encompasses a changing environment that encourages socialization, exercise, sensory and cognitive stimulation, and task-specific therapy targeting the primary impairment.…”
Section: Early Beginningsmentioning
confidence: 99%
See 4 more Smart Citations
“…EE alone is not effective in promoting recovery of skilled forelimb movements (e.g., reaching; Grabowski et al, 1993 ), since there is no opportunity to engage in this activity in standard EE configurations. As such, to fill this void our group adds a daily reaching task component to EE which dramatically improves the level of recovery provided by EE (Biernaskie and Corbett, 2001 ; Biernaskie et al, 2004 ; Jeffers and Corbett, 2018 ). Thus, the ideal definition of EE, unlike typical stroke rehabilitation in the clinic, encompasses a changing environment that encourages socialization, exercise, sensory and cognitive stimulation, and task-specific therapy targeting the primary impairment.…”
Section: Early Beginningsmentioning
confidence: 99%
“…Using a modified EE paradigm in which EE was combined with daily reach training (i.e., enriched rehabilitation, ER), it was found that EE, running exercise and reach training all produce a uniform pattern of activation throughout all layers of the sensorimotor cortex after stroke, however ER causes a more specific pattern of activation, targeting layer II and layer III motor neurons (Clarke et al, 2014 ). Recently, we showed that ER is more effective than either EE alone or reach training alone at restoring skilled forelimb function after stroke (Jeffers and Corbett, 2018 ). Similarly, others have shown a synergistic benefit when EE is paired with either resistance exercise or increased social interaction (Brenes et al, 2016 ; Prado Lima et al, 2018 ).…”
Section: Early Beginningsmentioning
confidence: 99%
See 3 more Smart Citations